Changing rural stratification system - Sharma, K. L. (Bangalore, 1974)
Stratification has a strategic importance in structural analysis of the society. It is a field where forces of social, economic and political changes are generated. The changes in the stratifica tion system imply reallocation of status, power and economic privileges. As such, the study of this problem constitutes the most important area of sociological analysis. So far a few studies on the changing patterns of stratification have been conducted systematically, whereas the holistic analyses of village communities abound. There are also numerous reports and monographs analysing specific systems and sub-systems of the rural society. With the exception of the works of F.G. Bailey (Caste and the Economic Frontier, 1957), Andre Beteille (Caste, Class and Power, 1966) and Ramakrishna Mukherjee (The Dynamics of a Rural Society, 1957), the focus on structural ana lysis and change has not been equally articulate in the literature on rural sociology in India.
a comperative study of six villages in Rajasthan, India
Keywords: Sociology